RELEVANSI HADIST TENTANG KASIH SAYANG DALAM PEMBINAAN HUBUNGAN GURU DAN MURID : Kasih Sayang; Hadis Nabi SAW; Hubungan Guru dan Murid; Pendidikan Islam; Karakter - Julita, Julita Hardianti; Anisa Noer Rahma; yusuf, Muhammad Yusuf Iskandar; Rendi, Muhammad Rendi Ramdhani (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2025)
This article outlines the importance of love as demonstrated by the Prophet Muhammad (peace be upon him) and its relevance to the interaction between educators and students in the realm of education. The aim of this article is to explore the application of the values of affection found in hadith in educational activities to create a warm, pleasant environment that helps build positive character in students. Data collected from the Quran, hadiths, Islamic books, as well as related journals and academic articles are used in this qualitative research. The results show that teachers who exhibit caring attitudes—such as being patient, gentle, and caring towards their students—are able to create harmonious relationships, enhance the learning spirit, and instill positive morals in their students. It is crucial to integrate these principles into the current education system as they can contribute to the development of a generation that is not only knowledgeable academically but also possesses strong ethics and concern for others